Students’ Common Errors in Constructing Simple¬-Past Tense Interrogative Sentences - Khofifah, Rizky; Lubis, Rica Umrina; Fitriani, Fitriani (MUDABBIR Journal Research and Education Studies, 2025)
This study analyzes common errors made by students in constructing simple past tense interrogative sentences, focusing on English language learners at STAIN Mandailing Natal who have completed the Intermediate Grammar course. This study uses a qualitative descriptive approach to analyze the types of errors that students often encounter when constructing simple past tense interrogative sentences, such as incorrect verb forms after the auxiliary verb “did”, confusion between positive, negative, and interrogative forms, and inappropriate placement of auxiliary verbs. The findings indicate that these errors stem from a lack of understanding of tense structures and a lack of practice in constructing interrogative sentences. This study highlights the importance of grammar in effective communication and suggests that teachers implement targeted teaching strategies to address these common errors. By identifying specific areas where students experience difficulties, this study aims to contribute to better teaching methods and improve students’ proficiency in using simple past tense interrogative sentences. Ultimately, this study underlines the importance of integrating grammar education into the English curriculum to foster better language acquisition and communication skills among learners.